Head-positioning with vibration suppression in hard disk drive systems - Ukakimaparn, Prapart; Tirasesth, Kitti; Pannil, Pittaya; Smerpitak, Krit; Trisuwannawat, Thanit; Shi, Yan (My University, 2012)
This paper proposed a controller design technique for controlling the movement of the head in the Hard Disk Drives (HDDs) system to any track accurately. The simulation results by modeling the HDDs as a two-mass system with a spring flexure controlled by the optimal H 2 with the derivative state constrained revealed that only these constraining weights are not enough to eliminate the steady state errors. To accomplish this task, the type of the system to be controlled was modified by adding an integrator; then the derivative state constrained optimal H 2 integral servo controller is applied. The HDD head position to any tracks with no offset and the vibrations are also to be suppressed as well. ICIC International © 2012.
Keywords: HDD control; Optimal H 2 integral servo control; Vibration suppression